How does Student Interest Influence Their Participation Pursuing Accounting Educational Profession? - Ika Dewi Hartutik; Kartika Hendra; Endang Masitoh (Shirkah: Journal of Economics and Business, 2016)
This purpose of this study is to determine the effect of career motivation, motivation quality, economic motivation, social motivation, and motivation on the interest of accounting students to enroll in education programs designed to produce professional accountants. Data analysis here involves descriptive statistics, classical assumptions, and hypothesis testing with multiple linear regression analysis. The results of the study clearly show (1) the motivation of career affects the interest of accounting students to follow PPAk; (2) quality motivation does not affect the interest of accounting students to follow PPAk; (3) economic motivation does not affect the interest of accounting students to follow PPAk; (4) social motivation does not affect the interest of accounting students to follow PPAk; (5) the degree motivation does not affect the interest of accounting students to follow PPAk. Keywords: motivation, interests, education accounting profession, PPAk